2001
DOI: 10.1523/jneurosci.21-08-02589.2001
|View full text |Cite
|
Sign up to set email alerts
|

The Surface Accessibility of the Glycine Receptor M2–M3 Loop Is Increased in the Channel Open State

Abstract: Mutations in the extracellular M2-M3 loop of the glycine receptor (GlyR) ␣1 subunit have been shown previously to affect channel gating. In this study, the substituted cysteine accessibility method was used to investigate whether a structural rearrangement of the M2-M3 loop accompanies GlyR activation. All residues from R271C to V277C were covalently modified by both positively charged methanethiosulfonate ethyltrimethylammonium (MTSET) and negatively charged methanethiosulfonate ethylsulfonate (MTSES), implyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
76
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 36 publications
10
76
0
Order By: Relevance
“…We propose that conformational changes occur in the spasmodic loop and Cys-loop of the GlyR upon ligand binding that are an important part of the process linking ligand binding to channel gating. This is consistent with the previous demonstration that the spasmodic mutation results in impaired receptor gating but does not affect ligand binding (19,20), and the M2-M3 linker is involved in channel gating (12)(13)(14).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We propose that conformational changes occur in the spasmodic loop and Cys-loop of the GlyR upon ligand binding that are an important part of the process linking ligand binding to channel gating. This is consistent with the previous demonstration that the spasmodic mutation results in impaired receptor gating but does not affect ligand binding (19,20), and the M2-M3 linker is involved in channel gating (12)(13)(14).…”
Section: Discussionsupporting
confidence: 93%
“…Effects of Double Charge Reversal Mutations-Charged residues located in the M2-M3 linker have previously been implicated in channel gating (12,13) and this study has demonstrated the role of loop 2 and loop 7 charged residues in gating. Therefore, we tested for electrostatic interactions between the negatively charged residues of loops 2 and 7, and the positively charged Lys-276 residue of the M2-M3 linker by creating the double reverse charge mutations E53K:K276E, D57K:K276E, and D148K:K276E.…”
Section: Resultsmentioning
confidence: 51%
See 2 more Smart Citations
“…Differences in the cysteine modification rate between the closed and open states may provide information about the associated structural changes. Our laboratory previously used this approach to demonstrate a glycine-induced increase in the surface exposure of six continuous residues (Arg 271 -Lys 276 ) in the GlyR M2-M3 linker domain (14). These residues lie mid-way between the binding site and the activation gate (7), and it is now well established that they experience a conformational change that is crucial for the activation of GlyRs (14 -18), ␥-aminobutyric acid, type A receptors (19 -24), and nAChRs (7,(25)(26)(27).…”
mentioning
confidence: 99%